STRATEGIC CHANGES IN CONSTRUCTION ENTERPRISES: CONCEPTUAL ESSENCE AND FACTORS OF INFLUENCE - MYKOLAICHUK, Iryna; ORAIEVSKYI, Anton (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The purpose of this article is to define the conceptual essence of strategic changes in Ukraine’s construction industry, to systematize internal and external factors influencing these processes, and to develop theoretical and methodological guidelines for effective change management under conditions of digital transformation and post-war recovery. The study applies a systemic and comparative approach, analytical and generalization methods, PESTEL analysis. The article examines the conceptual foundations of strategic changes in Ukraine’s construction industry under conditions of transformational economy and post-war recovery. The essence of “strategic change” is defined, and its main classifications and determinants are identified. The study analyzes current trends in the sector, including digitalization, implementation of innovative technologies, greening of production, and expansion of national reconstruction programs. Particular attention is paid to internal organizational factors such as human resource development, corporate culture, and innovation capacity. The article substantiates the role of strategic changes as a key mechanism for ensuring the resilience, adaptability, and competitiveness of construction enterprises. The findings aim to enhance managerial decision-making in strategic development and reconstruction of Ukraine’s construction sector. An analysis of the external environmental factors influencing strategic changes in construction industry enterprises has been carried out using the PESTEL analysis. The research contributes to refining the definition of “strategic change” in the context of the construction industry and proposes an adapted framework for managing such changes, emphasizing the role of digitalization, innovation, and human resources.
Keywords: changes; strategic changes; strategic change management; construction industry; influencing factors; PESTEL analysis; strategic development; innovations